Environmental Kuznets Curve in Transitioning Economies: Spatial Spillovers and Strategic Decoupling in Nepal - Adhikari, Bibhav; Shrestha, Rewat; Gurung, Jas Bahadur (Madhyabindu Journal, 2026)
The environmentalists, policymakers, and practitioners frequently confront on the issue of “can economy be green?” or “should follow the grow now and clean later strategy?”. However, Nepal has its own time-bound goal, such as to become a middle-income country by 2030 and net zero emissions by 2045. This goal further spreads the confusion among stakeholders. In this context, this study aims to evaluate the growth-emission nexus under the Environmental Kuznets Curve (EKC) hypothesis by employing Fully Modified Organized Least Square (FMOLS), Canonical Cointegrating Regression (CCR), regional panel analysis, spatial econometric analysis, and causal inference analysis. Using high-income simulation, study identifies an inverted U-shape with turning points of $37,000-$43,000 with income elasticity of -0.457. However, Nepal’s time series data (2005-2023, n=19) shows the positive income-emissions elasticity (+1.425), signaling the positive coupling and current nominal GDP is far below than the estimated turning points. This result exhibits the Nepal’s position on pre-peak of turning points. However, this study also identifies the effective framework consisting of hydroelectricity infrastructure, community forestry, and regional cooperation for strategic decoupling. This framework is tunneling through lever for transforming economies. These findings are crucial for policymakers to design and implement the integrated framework proactively, which ensures upgrading the income status of Nepal along with achieving net emission goal by 2045.